Natural Destruction And The Role Of Humans In Ongkak: A Collection Of Short Story By Spn. Fakrunnas Ma Jabbar (An Ecocritic Study) - Iin Agustina; Else Liliani; Anwar Efendi (Makassar State University, 2022)
Abstract. The environmental crisis is not a new topic. It is a phenomenon that we cannot ignore. Natural damage, forest fires, floods and others are caused by humans. Therefore, this study aims to find out the forms of natural damage and how the role of humans in providing defense in the short story entitled Ongkak: a collection of short stories by SPN. Fakrunnas MA Jabbar based on eco-critical theory, and tries to correlate research results with social phenomena that are currently happening. This research is a qualitative research, the data in this study were taken from short stories with environmental themes. The instrument in this study was the researcher as a human instrument assisted by notes. In analyzing the data, the researcher reads the short stories repeatedly and interprets it using ecocritical theory. This study found that some short stories use nature as mystical symbols, such as butterflies and trees, and some short stories show natural damage in the form of deforestation, flooding, infrastructure damage, fog, water pollution and tornadoes. The role of humans in overcoming natural damage occurs in the form of providing defense. The results of this research should be able to provide an impact in the form of insight and a sense of responsibility towards the importance of protecting nature. Keywords: Natural Damage, Ecocritic, Short Story